Jamur Makroskopis Di Hutan Lindung Gunung Nona Kota Ambon: Jenis, Frekuensi Keberadaan Keragamannya - desmiara simanjuntak; Jogeneis Patty; Costanza Uruilal (Fakultas Pertanian, Universitas Pattimura Ambon, Indonesia, 2026)
Macroscopic fungi are heterotrophic eukaryotic organisms with visible fruiting bodies that play important ecological roles as decomposers in forest ecosystems. The Gunung Nona Protected Forest in Ambon City provides favorable environmental conditions for fungal growth; however, information regarding the diversity and occurrence of macroscopic fungi in this area remains limited. This study aimed to identify species, analyze occurrence frequency, population abundance, and morphological diversity of macroscopic fungi in the Gunung Nona Protected Forest, Ambon City. The research was conducted from March to May 2025 using a survey method with five transect lines measuring 100 m × 10 m each. Species identification was based on fruit body morphology, while morphological diversity was analyzed using Hierarchical Cluster Analysis (HCA). The results revealed 32 species of macroscopic fungi, consisting of 31 species of Basidiomycota and 1 species of Ascomycota, belonging to 19 families. A total of 405 fruiting bodies were recorded during the study. Collybia sp. showed the highest occurrence frequency (100%), while Pachyella sp., Amanita ocreata, and Hygrophorus discoideus had the lowest frequency (20%). HCA grouped all species into two major clusters with a dissimilarity coefficient of 31%. These findings indicate that the Gunung Nona Protected Forest possesses high macroscopic fungal diversity and can serve as baseline information for conservation efforts and future fungal research in Maluku.